Shahid Javed Burki. Changing Perceptions, Altered Reality: Pakistan’s Economy under Musharraf, 1999-2006. Karachi: Oxford University Press, 2007. 373 pages. Hardbound. Price not given. (The Pakistan Development Review, 2009)
This book is another addition to Shahid Javed Burki’s work whose writings have been pivotal for understanding Pakistan’s social and economic transitions. The book examines various sectors of the economy that could become the source for sustainable growth. Thoughtful public policies in the high-potential areas are suggested with the claim that these could help the country join the ranks of Asia’s rapidly growing economies. Based on the weekly columns by the author published in the daily DAWN, and focusing on the 1999-2006 period, the tenure of President Pervez Musharraf, the book analyses the economic and social problems faced by Pakistan. It then discusses the opportunities that exist for the country in light of its geographical situation, and the rapid changes in the structure of the global economy. The issues explored in the book include the reasons for the rapid growth of the economy from 2003 onwards, as well as its impact on poverty and income distribution. It is suggested that these high rates of growth would not be sustained into the future unless a number of changes in the structure of the economy were introduced. The book consists of eight chapters. The first chapter starts with a brief discussion of the country’s economic history as well as the situation in mid 2000 (associated with high growth rates). It then continues to analyse the factors responsible for such growth with the caution that the economy still needs more measures before labeling it to have been set on a course of a high level of sustainable growth. In this regard the obstacles particularly related to infrastructure and governance are discussed raising crucial points and suggesting suitable measures. The chapter identifies various areas that need urgent attention by the policy-makers advising them to understand the true nature of the ‘determinants of growth’ and how they will affect the incidence of poverty and equality of opportunity.